Biosimilars in Focus: Evaluating Their Role Compared to Adalimumab in Clinical Practice - Dorota Waz; Michał Mazur; Jakub Szarłowicz; Zofia Goliszek; Karolina Łucja Sobek; Wiktoria Tabin-Barczak; Aldona Sokołowska; Klaudia Fikas; Kamil Chwaliszewski; Sebastian Samuła (Quality in Sport)
Introduction and Purpose: